Relative Sea Level Changes and Morphotectonic Implications Triggered by the Samos Earthquake of 30th October 2020 - Niki Evelpidou; Anna Karkani; Isidoros Kampolis (Journal of Marine Science and Engineering, 2021)
On 30th October 2020, the eastern Aegean Sea was shaken by a Mw = 7.0 earthquake. The epicenter was located near the northern coasts of Samos island. This tectonic event produced an uplift of the whole island as well as several cases of infrastructure damage, while a small tsunami followed the mainshock. Underwater and coastal geological, geomorphological, biological observations and measurements were performed at the entire coast revealing a complex character for the uplift. At the northwestern part of the island, maximum vertical displacements of +35 ± 5 cm were recorded at the northwestern tip, at Agios Isidoros. Conversely, the southeastern part was known for its subsidence through submerged archaeological remains and former sea level standstills. The 2020 underwater survey unveiled uplifted but still drowned sea level indicators. The vertical displacement at the south and southeastern part ranges between +23 ± 5 and +8 ± 5 cm suggesting a gradual fading of the uplift towards the east. The crucial value of tidal notches, as markers of co-seismic events, was validated from the outcome of this study. The co-seismic response of Samos coastal zone to the 30th October earthquake provides a basis for understanding the complex tectonics of this area.